Aplicação da eletrocinética em um solo tropical :análise da influência da mineralogia sobre o fluxo eletro-osmótico - Garcia, Juliana Fernandes dos Santos (2017)
The electrokinect technique was applied in a kaolinite soil, from the State of Rondônia. Homogenized and less rigid samples were reconstituted from the laboratory from unsistuberd samples and a mixture was then prepared for carrying out the present study. The mixture used in this study was representative of the originals soils. The experiments were conducted in a one – dimensional electrokinect cell with different phs. In addition to retention curve was determined with Hyprop equipment. The results indicates that the structure influenced the soil behavior during the electrokinect tests. The values of electrical resistivity were much lower when compared to results for structured soils. Regarding the geotechnical parameters, the samples presented liquidity and plasticity limits lower than the value without the addition of the technique. The ph of the solutions used had influence on the electroosmotic flow, not only in its magnitude but also in its direction.